PERAN CUSTOMER SATISFACTION SEBAGAI MEDIATOR PENGARUH SERVICE QUALITY TERHADAP CUSTOMER LOYALTY PADA PT. KARYA PAK OLES TOKCER DENPASAR - Ni Ketut Karwini; I Wayan gde sarmawa; Ni Kadek suryani (STIMI Handayani Denpasar, 2014)
Customer loyalty is a key factor and important in maintaining and increasing the company’s revenue growth and profitability. Therefore, almost allcompanies constantly strive to keep its customers to be loyal to the company. Someopinions and results of some studies found that the key of the company’s success isin maintaining customer loyalty, quality of services and customer satisfaction, so inthis study is intended to analyze the role of customer satisfaction as a mediator of theeffects of service quality on customer loyalty. This study is took place at a companyengaged in manufacturing of agricultural producers of traditional medicine andhealth, namely PT . Karya Pak Oles Tocker, located at Jalan Komodo No. 38 - XDenpasar - Bal . This research was supported by75 respondents who are determinedbased on a Slovin formula, and processed with Partial Least Square method throughSmartPLS 2.0 M3 , the first-order approach, with the 95% confidence level. Theresults showed that no significant effect of service quality on customer loyalty, butshowed a positive and significant effect on customer satisfaction. In other parts,customer satisfaction is a significant positive effect on customer loyalty.